A diperiodatoargentate(III)-based chemiluminescence determination of mitoxantrone in pharmaceutical preparations and human serum. Issue 2 (3rd April 2021) - Xue, Lili; Zhang, Min; Li, Guanghui; Cao, Jianhua; Yao, Hanchun
ABSTRACT: Chemiluminescence (CL) method, combined with the flow-injection (FI) technique, is an attractive alternative for pharmaceutical analysis. In this paper, a CL reaction between diperiodatoargentate(III) (DPA) and mitoxantrone (MTX) was observed. A strong CL signal was generated during the reaction of mitoxantrone with DPA in an alkaline medium. Thus a highly sensitive ﬂow injection CL method was developed for the determination of mitoxantrone. Optimized experimental conditions were investigated in detail. Under the optimum conditions, the relative CL intensity was linear with the mitoxantrone concentration in the range of 8.0 × 10 −10 –5.0 × 10 −7  g/mL with a correlation coefficient of 0.9994 and the detection limit was 1.9 × 10 −10  g/mL. The proposed method had good reproducibility with a relative standard deviation of 1.5% ( n  = 11) for 1.0 × 10 −7  g/mL mitoxantrone. The highly sensitive method was successfully applied to the determination of mitoxantrone in pharmaceutical preparation and serum samples with satisfactory results. The possible CL reaction mechanism was also discussed brieﬂy. GRAPHICAL ABSTRACT: UF0001